Residencies - Galichnik Art Colony Residency, In Collaboration with The National Gallery in Skopje - Antoniou, Klitsa (My University, 2026)
Residencies - Galichnik Art Colony Residency, In Collaboration with The National Gallery in Skopje In Collaboration with The National Gallery in Skopje Visual Intrusion Organizer and curator Ana Frangovska Galichnik, North Macedonia